Determinants of skilled based migration in sri lanka: evidences from panel data - Dharmadasa, R.A.P.I.S.; Dissanayake, N.K.R.; Herath, H.M.T.R. (University of Jaffna, 2019)
Skilled based migration has gained importance in recent years reflecting the impact of globalization, revival of growth within the economy and rapid growth in information and communication technology. By now, migration of skilled workers from developing countries has become a persistent trend. In Sri Lankan context, the most pressing issue is the mismatch of number of workers demanded by the foreign countries and supplied from Sri Lanka according to the level of skill. As a contribution to reduce the gap and to support government and policy formulating authorities, this research study examines the macroeconomic determinants of skilled based migration from Sri Lanka using gravity model of migration. Poisson Pseudo Maximum Likelihood (PPML) technique and gravity model was used as the estimation technique. Secondary data over the period of 2009 to 2017 were used to estimate the model along with destination year fixed effects. Empirical results clearly demonstrate that GDP per capita of Sri Lanka is the push factor which force the people to move from Sri Lanka while the destination country’s population, unemployment rate, age dependency ratio and political stability are the pull factors which attract migrants towards the destination. Furthermore, population of Sri Lanka and distance between two countries were also discovered as significant under the research study.
Keywords: Skill-based migration; Gravity model; Panel data; Poisson pseudo maximum likelihood technique; Fixed effects